Evaluation of patient‐focused interventions to promote colorectal cancer screening among New York State Medicaid managed care patients. Issue 21 (25th October 2018) - L. M. Dacus, Heather; L. Wagner, Victoria; A. Collins, Elisè; M. Matson, Jacqueline; Gates, Margaret; Hoover, Sonja; K. L. Tangka, Florence; Larkins, Teri; Subramanian, Sujha
Abstract : Background: The objective of this study was to evaluate an ongoing initiative to improve colorectal cancer (CRC) screening uptake in the New York State (NYS) Medicaid managed care population. Methods: Patients aged 50 to 75 years who were not up to date with CRC screening and resided in 2 NYS regions were randomly assigned to 1 of 3 cohorts: no mailed reminder, mailed reminder, and mailed reminder + incentive (in the form of a 25 cash card). Screening prevalence and the costs of the intervention were summarized. Results: In total, 7123 individuals in the Adirondack Region and 10, 943 in the Central Region (including the Syracuse metropolitan area) were included. Screening prevalence in the Adirondack Region was 7.2% in the mailed reminder + incentive cohort, 7.0% in the mailed reminder cohort, and 5.8% in the no mailed reminder cohort. In the Central Region, screening prevalence was 7.2% in the mailed reminder cohort, 6.9% in the mailed reminder + incentive cohort, and 6.5% in the no mailed reminder cohort. The cost of implementing interventions in the Central Region was approximately 53% lower than in the Adirondack Region. Conclusions: Screening uptake was low and did not differ significantly across the 2 regions or within the 3 cohorts. The incentive payment and mailed reminder did not appear to be effective in increasing CRC screening. The total cost of implementation was lower in the Central Region because of efficiencies generated from lessons learned during the first round of implementation in the Adirondack Region. More varied multicomponent interventions may be required to facilitate the completion of CRC screening among Medicaid beneficiaries. Abstract : Screening uptake is low in the New York State Medicaid population after the implementation of a multicomponent screening promotion intervention. Additional research is needed to determine whether the inclusion of additional points of contact yield improved screening rates. Cost efficiencies may be achieved through multiple rounds of interventions.